1996
DOI: 10.1006/viro.1996.0282
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycosylation of Hepatitis B Surface Antigens Is Involved but Not Essential in the Assembly of Hepatitis Delta Virus

Abstract: Hepatitis delta virus (HDV) is a defective virus requiring the hepatitis B virus (HBV) to provide hepatitis B surface antigens as the envelope protein. The hepatitis B surface antigens are posttranslationally modified by N-linked glycosylation, and its significance in HDV assembly was investigated with a cotransfection system using human hepatoma cell line Huh-7. After the N-linked glycosylation of HBsAg was blocked by tunicamycin treatment, the packaging of HDV in the culture system could be suppressed to a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…Furthermore, it has been suggested that a non-glycosylated Ag loop faces the cytoplasm, which possibly masks the cytosolic interaction sites with HDV or hinders appropriate connections between HBsAg and HDV (Figure 1) [11] . Due to deferent propagation responses of HBV and HDV to non-glycosylated Ag loop, it is possible that these viruses apply different mechanisms to interact with HBsAg [21] . Likewise, the lateral S-S interactions between S protein carbohydrates, which play a critical role in virion stability, are suggested to occur differently for HBV and HDV due to their particle sizes [12] .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, it has been suggested that a non-glycosylated Ag loop faces the cytoplasm, which possibly masks the cytosolic interaction sites with HDV or hinders appropriate connections between HBsAg and HDV (Figure 1) [11] . Due to deferent propagation responses of HBV and HDV to non-glycosylated Ag loop, it is possible that these viruses apply different mechanisms to interact with HBsAg [21] . Likewise, the lateral S-S interactions between S protein carbohydrates, which play a critical role in virion stability, are suggested to occur differently for HBV and HDV due to their particle sizes [12] .…”
Section: Resultsmentioning
confidence: 99%
“…In more detailed studies it was shown that N-glycosylation of S-HBsAg, which is mediated by the C-terminal domain of S protein and occurs partially on Asn-146, affects HDV envelopment and secretion [12] . Based on these studies, HDV secretion is delayed or reduced (about ten folds) in the presence of nonglycosylated HBsAg, while HBV and HBsAg formation is not affected [21] . Although a weakened interaction between HBsAg and other components of HDV-RNP complex (rather than L-HDAg) has been suggested for this reduction, based on the luminal positioning of Ag loop in the ER membrane, a direct interaction of this domain and HDV components is unlikely [21,27] .…”
Section: Shirvani-dastgerdi E Et Al Hbv-hdv Interactionsmentioning
confidence: 96%
See 3 more Smart Citations